X-ray diffraction and optical characterization of interdiffusion in self-assembled InAs/GaAs quantum-dot superlattices - Xu, S. J. (2013)
We report on the characterization of thermally induced interdiffusion in InAs/GaAs quantum-dot superlattices with high-resolution x-ray diffraction and photoluminescence techniques. The dynamical theory is employed to simulate the measuredx-ray diffraction rocking curves of the InAs/GaAs quantum-dot superlatticesannealed at different temperatures. Excellent agreement between the experimental curves and the simulations is achieved when the composition, thickness, and stress variations caused by interdiffusion are taken in account. It is found that the significant In–Ga intermixing occurs even in the as-grown InAs/GaAs quantum dots. The diffusion coefficients at different temperatures are estimated.